Pendampingan Tatakelola Menejemen Percetakan Pondok Pesantren Darussalam Sumbersari - Imam Murtadho; Miftahul Arif (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Printing is a very important means for an installation in supporting the success.a One form of effort that has been done by the Darussalam boarding school in succeeding the program is to form a Pesantren Owned Business Entity that moves in the Printing Sector.It makes the author interested in assisting printing in darussalam pesantren. Pondok Pesantren Darussalam, so that it can cause :(1) The creation of quality and propesional printing, (2) Can overcome the problem of printing management (3) It is expected that the printing board can make accountability report. The implementation of this mentoring activity has started from August 3 to August 27, 2020. The description of the assistance activities of Printing Management Management in The Darussalam Pesantren Kencong Kencong Kediri Support activities includes: (1) Human Resource Training (2) Distribution of printing results to Santri Pondok pesantren Darussalam (3) Administrative manufacturing training. Due to time and funding constraints, follow-up and monitoring of this devotional activity will be continued by BUMP under the assistance of the institution.